2018
DOI: 10.1007/s00455-018-9895-6
|View full text |Cite
|
Sign up to set email alerts
|

Dysphagia and Oral Morbidities in Chemoradiation-Treated Head and Neck Cancer Patients

Abstract: This study prospectively evaluated relationships between oral morbidities and swallowing ability in head/neck cancer patients following chemoradiation therapy (CRT) and at 3 months following CRT. Thirty patients with confirmed head/neck cancer undergoing chemoradiation were assessed with a battery of swallowing measures and measures of oral morbidities related to chemoradiation (xerostomia, mucositis, pain, taste/smell, oral moisture). All measures were completed at baseline (within the first week of CRT), at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 30 publications
0
28
0
1
Order By: Relevance
“…Dysphagia is among the most prevalent and debilitating symptoms resulting from HNC treatment. It has been reported that different mechanisms may contribute to the development and maintenance of dysphagia during HNC treatment (Ihara et al, 2018). The pattern in correlation between QOL and functional assessment items differed according to the time point after treatment.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Dysphagia is among the most prevalent and debilitating symptoms resulting from HNC treatment. It has been reported that different mechanisms may contribute to the development and maintenance of dysphagia during HNC treatment (Ihara et al, 2018). The pattern in correlation between QOL and functional assessment items differed according to the time point after treatment.…”
Section: Discussionmentioning
confidence: 96%
“…Common oral morbidities resulting from HNC treatment include oral pain, oral dryness, and altered taste and smell perception. One of the most prevalent and debilitating side effects of HNC treatment is dysphagia (i.e., swallowing difficulty) (Ihara et al, 2018) that may develop as both acute and chronic complication of HNC treatment (Hutcheson et al,2012;Van den Berg et al, 2014). Dysphagia has been reported in over 76% of HNC patients treated with concurrent chemotherapy (CRT).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 It should be noted, however, that both of these prior studies were conducted on patients >3 months post-CRT; a time when the acute effects of radiation such as mucositis and radiation dermatitis, which cause pain, excessive mucous production, and xerostomia, would have likely subsided. 5 It is plausible that at the early time point (one month post-CRT treatment completion) captured in this study, the etiology of dysphagia is multi-faceted, 26 with factors other than edema alone contributing to increased EAT-10 and DIGEST scores post-treatment. Inspection of the data plotted in Figures 2 and 3 visually confirms the regression results.…”
Section: Discussionmentioning
confidence: 99%
“…While other reviews have suggested good IC responses can allow for reduction in subsequent RT dosing, risk-based RT dose de-escalation was not used in this cohort of patients. Thus the feeding tube requirements were still significant in this population of patients but were not significantly worse compared to historical data for OPC patients in general, 22 although patient reported dysphagia may under-estimate physiologic assessment of dysphagia. 23 Our experience has defined patients with T3-4 tumors, those undergoing concurrent chemotherapy with radiation, current active smoking while on therapy, and baseline swallowing dysfunction or weight loss are more likely to have feeding tube placement; however, adherence to an aggressive swallowing program may reduce long-term dependency.…”
Section: The Table Shows the Percentage Of Patients Who Reported Any mentioning
confidence: 61%